Share
Explore BrainMass

FOIL Method

How do you simplify these 3 problems?

(3x-4)(x+5)

(x+2)(x²+x+5)

(x+1)(x³+4x²+7x+3)

What is foil? and how do you use foil to solve these?

(7-2y)(10-3y)

(5z-2)(5z+2)

(x-6)²

(2-3x6)²

Solution Preview

Solution:

(3x-4)(x+5)=3x^2+15x-4x-20=3x^2+11x-20
(x+2)(x²+x+5) =x^3+x^2+5x+2x^2+2x+10=x^3+3x^2+7x+10
(x+1)(x³+4x²+7x+3)=x^4+4x^3+7x^2+3x+x³+4x²+7x+3=x^4+5x^3+11x^2+10x+3

What is foil? and how do you use foil to solve ...

Solution Summary

Expressions are expanded using FOIL.

$2.19